The Congressional Representation of Muslim-American Constituents - Martin, Shane (Politics and religion, 2009)
Legislators' responsiveness to constituency preferences is an accepted cornerstone of American representative democracy. Focusing on key domestic anti-terrorism votes during the 109th Congress, this study explores whether or not the presence of Muslim-Americans in a district influenced House members' roll-call behavior. We apply and test two competing theories of representation: the congruence theory and the minority backlash hypothesis. Using original data on Muslim-American constituency size, our analysis indicates little evidence of a representational backlash and some evidence that both Democratic and Republican members are positively responsive in their roll-call behavior to the presence of Muslim voters in their districts.